Image of science in the evaluation practices of those involved in teaching physical sciences in Benin: Analysis of the content of the speeches - OKE, SEGBEGNON EUGENE (My University, 2020)
This article aims to characterize the knowledge subject to assessment in physical sciences at the baccalaureate in series C and D and to determine how this knowledge is dependent on the organization and institutional curricular evolution put in place. From the point of view of the method, on the one hand, we built a grid characterizing what is asked of the students of the C and D series at the baccalaureate in terms of analysis of the content of the elements of speech. Seven baccalaureate subjects served as support for this study with regard to the epistemological ideas conveyed on science. The results tend to show the conformity of the baccalaureate physical science assessment tests with the official prescriptions despite the changes which have occurred in them. In addition, the study has shown that the baccalaureate in the C and D series in physical sciences only assesses students' objects of reasoning, simple know-how and is hardly concerned with skills, epistemological objects such as the image of science, models and modeling necessary for problem solving. The implications must be questioned.
Keywords: evaluation; physical science; official programs